Ground Improvement with Jet Grouting Solutions at the New Cruise Terminal in Lisbon, Portugal. (2016) - Pinto, Alexandre; Tomásio, Rui; Marques, Gonçalo
Abstract: The "Terreiro do Trigo" dockyard, at the "Jardim do Tabaco", was filled in order to allow the construction of the new "Santa Apolónia" Cruise Terminal in Lisbon, at the Tagus River right bank. A load transfer platform (LTP), founded over jet grouting columns, allowed the construction of a 4, 2m height embankment, placed over a soft muddy alluvium layer (undrained shear stress lesser than 20kPa) with about 20m of average thickness. Vertical full scale load tests were performed in order to assess the possibility to incorporate the jet grouting columns, reinforced with steel micropiles, as foundation solution for the new Cruise Terminal building. The design criteria of the jet grouting columns, including the quality control and quality assurance, are presented, as well as the main results of the adopted monitoring and survey plan. The main results of the full scale load tests are pointed out. Finally, the technical and economic advantages of the adopted solutions, comparing with some more conventional ones, are presented.